The Roles of Profitability in Moderating The Effects of Managerial Ownership, Leverage, and Firm Size Toward Intellectual Capital Disclosure - Khosidah, Nasihotul; Wahyudin, Agus (Accounting Analysis Journal, 2019)
This research aims to analyze the effects of managerial ownership, leverage, and firm size on the intellectual capital disclosures accompanied profitability as moderated variable. The population in this research are the companies registered in the LQ45 Stock Index in 2015-2017 as many as 29 companies. This study used sampling with purposive sampling. Unit of analysis obtained as many 87 analysis. Data collection used documentation technique. Data analysis in this study used descriptive statistics and inferential statistics. Hypothesis testing used moderation regression analysis with difference absolute test. The results of this study indicated that leverage and firm size have a significant positive effect, while managerial ownership has no significant effect on the intellectual capital disclosures. Profitability significantly moderates the effect of leverage and firm size on the intellectual capital disclosures while it does not significantly moderate the effect of managerial ownership on the intellectual capital disclosures. The conclusion of this study is that investors can consider leverage and firm size in investment decision making, considering the disclosure of intellectual capital in this study is influenced by leverage and firm size.